2013
DOI: 10.1016/j.virol.2012.11.013
|View full text |Cite
|
Sign up to set email alerts
|

IRES-based Venezuelan equine encephalitis vaccine candidate elicits protective immunity in mice

Abstract: Venezuelan equine encephalitis virus (VEEV) is an arbovirus that causes periodic outbreaks that impact equine and human populations in the Americas. One of the VEEV subtypes located in Mexico and Central America (IE) has recently been recognized as an important cause of equine disease and death, and human exposure also appears to be widespread. Here, we describe the use of an Internal Ribosome Entry Site (IRES) from encephalomyocarditis virus to stably attenuate VEEV, creating a vaccine candidate independent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 35 publications
1
44
0
Order By: Relevance
“…The distance between residue I121 (shown in green) and residue W64 (shown in red) on two different E2 subunits of the trimer is 13 Å. (64) 158 (24) 115 (17) 151 (28) 0 (2) 175 (52) 106 (24) 128 (15) (42) 135 (25) 105 (14) 123 (54) 3 (4) 123 (17) 122 (12) 108 (19) Immunoreactivities are expressed as a percentage of the immunoreactivity of the wild type, with ranges (maximum minus minimum values) given in parentheses. Values shaded in gray are for critical residues.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance between residue I121 (shown in green) and residue W64 (shown in red) on two different E2 subunits of the trimer is 13 Å. (64) 158 (24) 115 (17) 151 (28) 0 (2) 175 (52) 106 (24) 128 (15) (42) 135 (25) 105 (14) 123 (54) 3 (4) 123 (17) 122 (12) 108 (19) Immunoreactivities are expressed as a percentage of the immunoreactivity of the wild type, with ranges (maximum minus minimum values) given in parentheses. Values shaded in gray are for critical residues.…”
Section: Figmentioning
confidence: 99%
“…there are no specific prophylactics or therapeutics for CHIKV, any other alphaviruses, or the long-term diseases that they cause, with current treatments primarily consisting of anti-inflammatory drugs and antiviral compounds with broad spectra of activity (13)(14)(15). Although vaccine candidates against CHIKV were first proposed 45 years ago and vaccines against CHIKV are in active development (16)(17)(18)(19)(20)(21), many vaccine candidates tested to date have either failed to induce protective antibodies or demonstrated significant safety issues (22). As a result, many questions remain to be answered to understand the most protective human immune response to this virus.…”
mentioning
confidence: 99%
“…Charles et al (1997) showed that upon subcutaneous administration of a live attenuated recombinant vaccine candidate V3014, spread occurs to lymphoid tissues without causing viraemia and induces a VEEV-specific IgA response sufficient for protection against aerosol challenge with the virulent V3000 infectious clone. Rossi et al (2013) also used these mice as a model to test second-generation IRESbased vaccine candidates. Here, mice infected with virulent 68U201 strain by subcutaneous inoculation developed paralysis and extreme lethargy by day 2 post-infection and did not survive.…”
Section: A Taylor and Othersmentioning
confidence: 99%
“…Most vaccinated animals developed neutralizing antibodies within 3 weeks and maintained a high level of antibody titres for up to a year post-vaccination, sufficient to protect them from lethal challenge. Rossi et al (2013) also developed a highly sensitive in vivo model to test the attenuation of vaccine candidates, in which 6-day-old CD-1 mice received vaccines intracranially. Although vaccines were well tolerated in adult mice, all pups died after inoculation.…”
Section: A Taylor and Othersmentioning
confidence: 99%
“…Targeted insertion into these viruses of hundreds of point mutations that change codon usage without changing protein sequence greatly reduced the virulence but not the immunogenicity of live vaccine candidates. A second example of a rational attenuation strategy that targets the level and balance of protein production without altering protein sequence is that of internal ribosome entry site (IRES)-based attenuation developed for the alphaviruses Chikungunya virus (3) and Venezuelan equine encephalitis virus (4)(5)(6). It involved replacement of the alphaviral subgenomic promoter with an IRES of Encephalomyocarditis virus (EMCV).…”
mentioning
confidence: 99%